The Burden of Progressive-Fibrosing Interstitial Lung Diseases - Cottin, Vincent; Teague, Rhiannon; Nicholson, Lindsay; Langham, Sue; Baldwin, Mike (Frontiers in Medicine, 2022)
Despite conventional treatment, a proportion of interstitial lung disease (ILD) patients develop a progressive phenotype known as ‘fibrosing ILD with a progressive phenotype’ (PF-ILD), characterized by worsening respiratory symptoms, decline in lung function, and early mortality. This review describes the epidemiology, and the humanistic and economic burden of PF-ILDs other than idiopathic pulmonary fibrosis (non-IPF PF-ILD). A structured review of the literature was conducted, using predefined search strategies in Ovid MEDLINE and EMBASE, and supplemented with grey literature searches. The search identified 3002 unique articles and an additional 3 sources were included from the grey literature; 21 publications were included. The estimated prevalence of non-IPF PF-ILD ranges from 6.9 to 70.3/100000 persons and the estimated incidence from 2.1 to 32.6/100000 person-years. Limited evidence demonstrates that PF-ILD has a significant impact on patients’ quality of life, affecting their daily lives, psychological well-being, careers, and relationships. PF-ILD is also associated with significant economic burden, demonstrating higher healthcare resource use and direct costs compared with the non-progressive phenotype, and indirect costs, which include job losses. This review indicates that PF-ILD places a considerable humanistic burden on both patients and caregivers, and a substantial economic burden on healthcare systems, patients, and society.